The Long-Run Effects of Individual Debt Relief - Gustaf Bruze; Alexander Kjær Hilsløv; Jonas Maibom (CESifo GmbH, 2024)
Individuals with extensive debt may be granted debt relief in court. We provide a comprehensive evaluation of the Danish debt relief program with data from court records linked to nationwide register data. Using event-study methods and quasi-random assignment of applicants to court trustees with varying admission rates, we show that debt relief leads to a large increase in earned income, employment, assets, real estate, secured debt, home ownership, and wealth that persists for more than 25 years after a court ruling. The net transition of workers into employment accounts for two thirds of the increase in earned income.
Keywords: D14; D31; K35; 330; debt relief; personal bankruptcy; household finance